2006
DOI: 10.1016/s1569-9056(06)60264-9
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Testicular Microlithiasis?: Results of an Uk-Based National Questionnaire Survey

Abstract: Background: The association of testicular microlithiasis with testicular tumour and the need for follow-up remain largely unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…A large survey of British Urologists showed that one‐third of them performed follow‐up of men with TM (Ravichandran et al. , 2006).…”
Section: Follow‐upmentioning
confidence: 99%
“…A large survey of British Urologists showed that one‐third of them performed follow‐up of men with TM (Ravichandran et al. , 2006).…”
Section: Follow‐upmentioning
confidence: 99%
“…A lack of consensus exists regarding the preferred followup of microlithiasis in patients without a concurrent neoplasm, and thus many differing recommendations can be found in the literature and in practice [10]. Most authors agree that at least an annual physical examination and scrotal sonography are prudent.…”
Section: Solution To Practice Questionmentioning
confidence: 99%